Peter Salner: Premeny židovskej Bratislavy [Changes in Jewish Bratislava] : Bratislava: Albert Marenčin PT, 2008, 175 s., ISBN 978-80-89218-83-7. - Soukupová, Blanka (Lidé města, 2009)
A review of the book by Peter Salner.